Analysis of Waiting Period for Men after Divorce Perspective of Jamaluddin Aṭiyah's Maqaṣid Sharia Theory - Hasanuddin Hasanuddin; Muhammad Syukri Albani Nasution; Imam Yazid (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2021)
The Director General of Islamic Religious Institutional Development again issued Circular Number P-005 / DJ. III/Hk.00.7/10/2021 concerning marriage during the iddah period, according to the provisions of the circular "an ex-husband man can marry another woman when the iddah period of his ex-wife has ended". This article attempts to further analyze the waiting period for men due to talak raj'i divorce using Jamaluddin Aṭiyah's theory of maqashid as-sharia. This research is normative legal research. In the perspective of Maqashid As-Sharia proposed by Jamaluddin Aṭiyah, the regulation of waiting periods for men after divorce not only reflects aspects of Islamic law governing divorce, but also serves as a means to achieve broader goals in the lives of individuals, families, communities, and humanity by Islamic values. With this approach, the regulation has a profound impact on various aspects of life-related to divorce.